THE CONCEPTS OF ISLAMIC EDUCATION ACCORDING TO Q.S. LUQMAN VERSES 13-19 - Paiman, Ahmad (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to describe the role of parents in children's education according to Islam based on the analysis of the interpretation of Luqman's letter. The approach used is qualitative with a descriptive research type. The primary data sources used are the Koran and its translations and the book of Ibnu Katsir's interpretation. Collecting data using descriptive analysis method. The results of the research from the analysis of the interpretation of Surah Luqman verses 12-19 show that Luqman in carrying out his role as a parent is: to be a role model for his children by using exemplary education methods and methods of advice. As for the educational content contained in Surah Luqman verses 13,17,18,19, namely, do not associate partners with Allah, every action you take will be reciprocated, establish prayer, do good, resist evil, be patient, do not look away, do not be arrogant, be simple in walking. , and soften the sound. Thus it can be concluded that there is the role of parents as role models in sura luqman verses 13, 16, 17, 18, and 19 using educational methods with advice and educational methods by example and there is content of aqidah education, worship education, and moral education.